PENGEMBANGAN DAN PEMEROLEHAN BAHASA PADA ANAK USIA DINI YANG MENGALAMI GANGGUAN KOMUNIKASI - Hardianika Rahmaningtyas; Lina Putrianti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
In communicating, language is a very important component. Language acquisition in early childhood is clearly related to the continuity of children's lives both now and in the future. Many children at an early age have communication disorders in language acquisition. The aims of this research are 1) to determine the stages in language acquisition in early childhood, 2) to determine the influence of the environment on language acquisition in early childhood who experience communication disorders. The methodology used in this research is literature or library research. The results of the research show that the stages of early childhood language acquisition include acquiring vocabulary in the form of basic vocabulary including verbs, adjectives, nouns, number words. Apart from that, young children also begin to acquire derivative vocabulary, for example prefix affixes, suffix affixes, infix affixes and confix affixes. Environmental influences on early childhood language acquisition include parents or the family environment, school, and living environment.